2019
DOI: 10.1097/md.0000000000018028
|View full text |Cite
|
Sign up to set email alerts
|

Association between TGF-β1 rs1982073/rs1800469 polymorphism and lung cancer susceptibility

Abstract: Background: There have been several case–control studies to assess the relationship between the transforming growth factor-β1 (TGF-β1) T + 869C (rs1982073)/C-509T (rs1800469) gene polymorphism and lung cancer in recent years; however, the results remain controversial. In this study, we investigated the potential correlation between the TGF-β1 T + 869C/C-509T polymorphism and increased risk of lung cancer through meta-analysis. Methods: We searched the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Similarly, for C509T polymorphism, no significant association was found for breast cancer risk [27]. Another study done by Chen et al concluded that the TGFB1 T869C (rs1800470) and C509T (rs1800469) polymorphisms were not associated with lung cancer development and revealed the C509T (rs1800469) polymorphism diminishes the danger of lung cancer growth in patients with non-small cell lung cancer (NSCLC) [14]. Furthermore, a meta analysis study reported that in people of Asian ethnicity, C509T polymorphism was associated with lower risk of breast and gastric cancer, whereas, T869C polymorphism showed higher risk of developing cancer in Caucasian population but not in Asian people [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for C509T polymorphism, no significant association was found for breast cancer risk [27]. Another study done by Chen et al concluded that the TGFB1 T869C (rs1800470) and C509T (rs1800469) polymorphisms were not associated with lung cancer development and revealed the C509T (rs1800469) polymorphism diminishes the danger of lung cancer growth in patients with non-small cell lung cancer (NSCLC) [14]. Furthermore, a meta analysis study reported that in people of Asian ethnicity, C509T polymorphism was associated with lower risk of breast and gastric cancer, whereas, T869C polymorphism showed higher risk of developing cancer in Caucasian population but not in Asian people [28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reports of elevated expression of TGFB1 protein in patients with cervical adenocarcinoma are also available [12]. Polymorphisms of TGFB1 gene has been reported in different types of cancer including lung cancer and colorectal cancer [13,14] but its relation to the risk of developing cervical cancer in Bangladeshi population is not yet available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with the TT genotype have a slightly lower incidence of lung cancer compared to individuals with the other genotypes, suggesting a possible protective role of the TT variant for lung cancer susceptibility in patients with NSCLC. (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is mainly caused by smoking and other environmental factors, such as exposure to heavy metals, radiation, asbestos, and air pollution ( 3 ). However, even if exposed to these factors, only a small portion of people suffer from lung cancer, which indicates that genetic factors also play an important role in the occurrence of lung cancer ( 4 ). The current view is that the occurrence and development of lung cancer is the result of the interaction between environment and heredity ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%